A Study Of Electrical Equipment Life Analysis Influenced By Unbalanced Load Use - Widya Septiyani Br Ginting; Wahyu Desmandra; Syahrial Fauzi; Juan Daniel Siahaan; Solly Aryza (INFOKUM, 2025)
The use of unbalanced electrical loads in power systems can significantly impact the lifespan of electrical equipment. Load imbalance often occurs in power distribution systems serving various types of consumers with diverse consumption patterns. This study aims to analyze the effect of unbalanced load usage on the lifespan of electrical equipment, such as transformers, cables, and protection devices. The methodology involves measuring electrical parameters such as current, voltage, and power factor under balanced and unbalanced load conditions. Operational data are processed to determine the level of imbalance and its effects on temperature rise, power losses, and equipment efficiency degradation. The analysis is complemented with simulation models to predict equipment lifespan reduction based on thermal and electrical standards. The results indicate that load imbalance leads to a significant increase in operating temperatures, particularly in transformers and cables, accelerating insulation degradation. Additionally, load imbalance increases power losses, reducing overall system efficiency. This study concludes that better load management to achieve balance can extend the lifespan of electrical equipment and improve the reliability of power systems.